Penetration Form of Inter-Hole Cracks under Double-Hole Blasting Conditions with Inclined Fissures - Shiwei Shen; Yue Zhao; Chang Liu; Shulin Dai; Fei Wu; Man Jiang (Advances in Civil Engineering)
During blasting construction in tunnel engineering, an inclined fissure near the blast hole produces the “Z” type of over-excavation and subsequently affects the overall blasting effect and stability of the tunnel. In this work, dynamic caustics testing was used to study the burst propagation mode and penetration form of explosive cracks at different positions between holes under double-hole blasting conditions. Results showed that the existence of gently inclined cracks changed the propagation law of explosive stress wave. The dominant fracture surface was formed in the vertical direction between the borehole and the fracture. Finally, the crack penetrates to form “Z”-type over-excavation, which was analyzed by the dynamic caustics test. The expansion velocity of the burst crack reached the maximum under the reflection of the explosion stress wave and then decreased with the attenuation of the stress wave intensity. The peak propagation velocity decreased with the increasing vertical distance between the prefabricated fracture and the borehole, and the stress intensity factor at the crack tip immediately reached its peak value after detonation, and the oscillation then decreased. These research results can serve a basis for reducing tunnel blasting over-excavation under this condition and optimizing blasting parameters.